P–683 Correlation of vitamin D deficiency with anti-Mullerian hormone (AMH) among infertile women in comparison to fertile women in a tertiary health facility in North-Western Nigeria. (6th August 2021) - Lawal, B; Adesiyun, A; Manu, M; El-Bashir, J; Olorukooba, A; Ladan, A; Sulayman, H
Abstract: Study question: is there correlation between Vitamin D Deficiency and AMH levels in infertile and fertile women? Summary answer: there is no significant correlation between Vitamin D deficiency and AMH levels in both infertile and fertile women What is known already: Vitamin D deficiency and insufficiency is a global health problem affecting over a billion people with higher prevalence among reproductive-age women, and blacks. Vitamin D is well known to play significant role in calcium-phosphate homeostasis and bone metabolism, however, recent studies have demonstrated diverse expression of vitamin D receptors in reproductive organs. This suggest the probable role of vitamin D in reproductive physiology and fertility. The pathogenesis of vitamin D in infertility is poorly understood, but thought to involve hypothalamo-pituitary axis, ovarian folliculogenesis and uterine implantation. Most studies are done in Assisted Reproduction Technology and in developed countries Study design, size, duration: A case-control study that involved 128 consecutively consenting women within the reproductive age group; 64 infertile women as the cases and 64 age and body mass index (BMI) matched fertile women as the controls. The study was conducted over a period of six (6) months Participants/materials, setting, methods: The study was conducted in Obstetrics and Gynaecology and Chemical pathology departments of Ahmadu Bello University Teaching Hospital Zaria, a tertiary hospital in North-Western Nigeria. It involved all cases of female-factor infertility as cases, while the controls were fertile women from 6 weeks postpartum to 1 year. Venous blood samples were assayed for serum 25(-hydroxy) vitamin D and AMH levels using Enzyme-Linked Immunosorbent Assay (ELISA) and data analysed with level of significance set as < 0.05 Main results and the role of chance: The mean ± standard deviation (SD) of serum Vitamin D levels in the infertile women and fertile women were 17.01 ± 7.61ng/ml and 11.34 ± 6.12ng/ml respectively, significantly higher in the infertile women (p-value <0.000). The prevalence of Vitamin D deficiency (<20ng/ml) was found to be significantly higher in the fertile women compared to infertile women (89.1% versus 68.8%; p-value 0.007). Vitamin D levels were found to be positively correlated with age (r 0.374; p-value 0.002) and parity (r 0.338; p-value 0.006). There was no association between vitamin D with type of, and causes of infertility. Vitamin D deficient women were found to be 6.5 times less likely to be infertile than non-deficient women (aOR 95% confidence interval 1.96–21.55; p-value 0.002). There was no significant correlation between vitamin D and AMH levels in vitamin D deficient women of both study groups (rs 0.180; p-value 0.242 and rs 0.088; p-value 0.521). Interestingly, there was significant relationship between AMH levels and causes of infertility (p-value 0.001), with higher levels of AMH found in infertile women with polycystic ovarian syndrome Limitations, reasons for caution: There is no consensus on the cut-off values for vitamin D levels as it relates to fertility, and no reference values for vitamin D deficiency and AMH levels in study area. The sample size was limited by cost, and the study was conducted in a single study area Wider implications of the findings: The vitamin D levels in women with infertility was low but yet not significantly correlated with AMH. Overall, prevalence of vitamin D deficiency among reproductive-age women was found high. There is need for life-style and dietary modifications. Further researches are needed to ascertain the effect of vitamin D on fertility. Trial registration number: Not applicable